Primary prostatic Burkitt’s lymphoma complicated with hemophagocytic lymphohistiocytosis: a case report and literature review - Guo, Xiong; Ai, Wei; Zhang, Zhi; Liu, Zonglai; Fu, Haibo; Gao, Pan; Liu, Fajun (Frontiers in Oncology, 2025)
This article reports a very rare case of primary prostatic Burkitt’s lymphoma. After transurethral resection of the prostate, the patient developed hemophagocytic lymphohistiocytosis, which rapidly progressed, leading to the patient’s death. Unfortunately, a definitive diagnosis was made only in the advanced stages of the disease, contributing to a delay in diagnosis and worsening of the patient’s condition. This report aims to improve the understanding of this disease and aid in its early recognition.